Complete continuum of care for maternal health services and determinants among mothers who gave birth in the last year in Chiro City, Eastern Ethiopia: a community-based cross-sectional study (2024) - Ali, Mohammed Ahmed; Geremew, Habtamu; Abate, Alegntaw; Bamlaku Golla, Eyasu; Simegn, Mulat Belay; Kumbi, Hawi; Gichew Wondie, Smegnew; Abdisa, Samuel; Legasu, Temesgen Dessalegne; Chekole, Moges Sisay (Frontiers in Global Women's Health, 2024)
IntroductionEthiopia has one of the highest maternal death rates in the world, with 412 deaths for every 100,000 live births. A qualified healthcare professional's care during pregnancy, delivery, and the postnatal period is crucial to saving the lives of the mother and her child. The continuum of maternity health services in Ethiopia is still shallow, despite efforts to increase the use of these services. This study's goal was to evaluate the magnitude and factors influencing the entire continuum of care for maternal health services in Chiro City in 2024.MethodsA community-based cross-sectional study was conducted from 15 January to 15 February 2024, among mothers who gave birth in the last year preceding the data collection period in Chiro City, Eastern Ethiopia. Data were collected through face-to-face interviews using a structured questionnaire. Multivariable logistic regression analysis was done to identify determinants of the complete continuum of care. A P-value of <0.05 was considered statistically significant in this study.ResultThe prevalence of a complete continuum of care among mothers who gave birth in the last year in Chiro District was 37.0%. Accordingly, women who received ANC were 5.24 times more likely to complete the maternal health services continuum of care compared with their counterparts (AOR: 5.24, 95% CI: 1.94, 14.15). Compared with their counterparts, women who received health education were 4.36 times more likely to complete the continuum of care (AOR: 4.36, 95% CI: 2.0, 9.51). Similarly, women who had planned pregnancies were 4.32 times more likely to complete the maternal health services continuum of care than those who had unplanned pregnancies (AOR: 4.32, 95% CI: 2.38, 7.85).Conclusion and recommendationThe continuum of care was favorably correlated with ANC usage, health education, and planned pregnancies. To increase the coverage of the entire continuum of maternal care, it is desirable to develop programs that encourage women to initiate ANC contacts, provide health education, and promote planned pregnancies.